Total Removal of a Suprasellar, Preinfundibular Retro Chiasmatic Craniopharyngioma via an Endoscopic Endonasal Approach: A Surgical Case Report - Alessandra Alfieri; Paola Flavia Schettino; Armando Rapanà; Ferdinando Caranci (Medical Science: Trends and Innovations Vol. 12, 2025)
Craniopharyngiomas are benign tumors (WHO Grade I) that occur both in children and adults. These tumors typically arise in the suprasellar region of the brain and affect the hypothalamus, the optic chiasm, the cranial nerves, the third ventricle, and the intracranial vessels. Because of their location, they can require challenging clinical and surgical management. In fact, often, because of the presence of calcifications, of a capsule very strongly adherent to neurovascular structures, of the relationship with hypophysis, pituitary stalk, chiasm, carotids, the circle of Willis, basilar artery, and third ventricle, the risk of mortality and morbidity is still mandatory. Various surgical techniques have been proposed: transcranial, transsphenoidal, and supraorbital approaches for surgical resection and treatment of craniopharyngiomas. Still, there is no common consent, but often the endonasal transsphenoidal extended procedures are considered the gold standard in many cases. This study presents a surgical technique of a case of complete surgical removal of an infundibular and retro-chiasmatic craniopharyngioma, via an endoscopic endonasal transphenoidal transplanum approach. In 2015, in the Department of Neurosurgery of the S. Anna and S. Sebastiano Hospital of Caserta, Italy, a 63-year-old woman was referred with bitemporal hemianopia and hypocorticoadrenalism. MRI revealed a suprasellar lesion with intracranial and retro-chiasmatic extension, heterogeneous texture, and a combination of solid, cystic, and calcified components. The patient was operated on using an extended endonasal endoscopic transphenoidal tranplanum approach. After the surgery, the visual deficit improved, and the patient was discharged 5 days after surgery without any complications. Despite advancements in surgical techniques, craniopharyngioma treatment remains demanding. There is still no consensus on the best surgical treatment, even if many authors prefer the endoscopic endonasal extended procedures because of a direct anatomic approach to neurovascular structures and a reduced morbidity to brain structures.